2022
DOI: 10.1177/1098612x221098718
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and response to treatment in cats with hypersomatotropism: the owners’ point of view

Abstract: Objectives The aim of this study was to collect clinical information from owners of cats with hypersomatotropism (HS) distributed worldwide, assessing the impact of HS and its treatments on cats’ quality of life (QoL) and survival time. Methods A survey focused on clinical presentation, diagnostic procedures, treatments, cats’ QoL and disease progression was distributed worldwide to owners of cats with HS. The owner’s perception of the cats’ QoL before and after or during treatment was defined using a score ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…[26][27][28] In a recent study on quality of life in cats with HST, another seven cases of acromegaly without DM were mentioned. 29 Two studies have indicated that the prevalence of hyperthyroidism in the population of diabetic cats is around 5-6%. 11,13 One study concluded that cats with induced hyperthyroidism have impaired glucose tolerance, possibly due to an increase in insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28] In a recent study on quality of life in cats with HST, another seven cases of acromegaly without DM were mentioned. 29 Two studies have indicated that the prevalence of hyperthyroidism in the population of diabetic cats is around 5-6%. 11,13 One study concluded that cats with induced hyperthyroidism have impaired glucose tolerance, possibly due to an increase in insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“… 26 28 In a recent study on quality of life in cats with HST, another seven cases of acromegaly without DM were mentioned. 29 …”
Section: Discussionmentioning
confidence: 99%
“…As improved quality of life is the key outcome when managing a patient, hypophysectomy seems to be the treatment of choice. 69 it is likely that improved iGF1 control with hypophysectomy has unseen effects, which result in quality-of-life improvement…”
Section: Journal Of Feline Medicine and Surgerymentioning
confidence: 99%
“…As improved quality of life is the key outcome when managing a patient, hypo-physectomy seems to be the treatment of choice. 69 It is likely that improved IGF1 control with hypophysectomy has unseen effects, which result in quality-of-life improvement that extends beyond effective control of diabetes mellitus. See the 'Factors affecting serum IGF1 concentration' box for a discussion of practical considerations when interpreting IGF1 values.…”
Section: Treatment Approachesmentioning
confidence: 99%